A Sartrean Approach to Ayé Ṣίṣe in Yorùbá Existentialism - Babalọla Joseph Balogun (Yoruba Studies Review)
The place of the world in the life of individual human being cannot be underestimated. This fact has culminated in the high esteem in which the concept of the world is held in the existentialist thinking. Using the Sartrean existentialist methodological approach, the paper critically examines the notion of the world (ayé) in the existentialist thinking of the Yoruba people of Nigeria. The paper argues that although humans find themselves thrown into the world (ayé) amidst situations that are not of their own making, sometimes amidst untoward circumstances, the right mark of an authentic existence is ṣíṣe ayé which literally means “doing the world”, rather than mere gbígbé ayé, that is, living in the world. The paper concludes that the hallmark of authentic existence is to be found in the act of “doing the world” rather than just living in it.